MARKETING ORIENTATION AND THE DEVELOPMENT OF SMALL AND MEDIUM ENTERPRISES IN CROSS RIVER STATE (Journal of the Management Sciences, 2024)
This study examined marketing orientation and the development of small and medium enterprises (SMEs) in Cross River State. It specifically sought to determine the effects of customer focus, product innovation, competitor analysis and integrated marketing communication on the development of SMEs in Calabar. The study adopted cross-sectional survey research design. A structured questionnaire was used to obtain primary data from 318 operators of SMEs in Calabar. Descriptive statistics were applied for data analysis and interpretation, while the hypotheses developed for the study were tested using multiple linear regression in the Statistical Package for the Social Sciences (SPSS 23). The findings of the study revealed that customer focus, product innovation, competitor analysis and integrated marketing communication had significant positive effects on the development of SMEs in Calabar. Hence, the study recommended the following, among others: operators of SMEs in Nigeria need to commit to the principle and practice of customer sovereignty in their operations by ensuring that goods and services they offer are tailored to satisfactorily meet customers’ needs on a consistent basis while maintaining a viable relationship with customers for the long term; SMEs should commit to continuous product innovation by conducting trend analysis in order to provide products that align with customers’ requirements and offer the most benefits to customers, thereby encouraging customer satisfaction and loyalty; and it is imperative for operators of SMEs to harness the potential of periodic competitor analysis to design and implement marketing campaigns to counter competitors’ actions, attract customers’ patronage and capture substantial market share.
Keywords: Marketing orientation, SMEs, Customer focus, Product innovation, Competitor analysis